Influence of opposition team formation on physical and skill-related performance in a professional soccer team - Carling, C. (European Journal of Sport Science, 2011)
This study examined the influence of opposition team formation on physical and skill-related performance in a professional soccer team. Performance in 45 French League 1 matches played over three competitive seasons (2007-2008, 2008-2009, and 2009-2010) was analysed using multi-camera computerized tracking. Players (n=21) in the reference team (using a 4-3-3/4-5-1 formation) were analysed in matches against three opposition team formations: 4-4-2 (11 games), 4-3-3/4-5-1 (16 games), and 4-2-3-1 (18 games). Performance was compared for defending and midfield units as a whole and individually across four positions: full backs, central defenders, central midfielders, and wide midfielders. Collectively, players covered a greater total distance (P<0.05) and distance in low- to moderate-intensity running (0-14.3 km · h-1) (P<0.05) in matches against a 4-2-3-1 compared with a 4-4-2 formation. Distance covered in high-intensity (14.4-19.7 km · h-1) and very high-intensity running (=19.8 km · h-1) was not affected by opposition formation. In contrast, players covered more distance in total high-intensity performance (=14.4 km · h-1) when the reference team was in possession against a 4-4-2 compared with a 4-2-3-1 formation (P<0.05), while a greater distance was run at these speeds when the reference team was not in possession against a 4-2-3-1 (P<0.01) and a 4-3-3 (P<0.05) compared with a 4-4-2 formation. Players ran less distance at low-to-moderate intensities in the second- versus first-half of matches against all three formations (P<0.01 to P<0.05), whereas total distance and high-intensity performance were unaffected. None of the measures of physical performance across the individual playing positions were affected by opposition team formation. Skill-related performance varied according to opposition formation: players as a whole performed more passes versus a 4-4-2 than a 4-2-3-1 formation (P<0.01); ground and aerial duels versus a 4-2-3-1 compared with a 4-4-2 formation (both P<0.01); one-touch passes versus a 4-2-3-1 compared with a 4-4-2 formation (P<0.01) and a 4-3-3/4-5-1 formation (P<0.05). The mean number of touches per possession was highest versus a 4-4-2 compared with a 4-3-3/4-5-1 (P<0.01) and a 4-2-3-1 formation (P<0.01). While skill-related performance across the four individual playing positions was generally unaffected by opposition team formation, mean pass length was greater for central midfielders against a 4-4-2 compared with a 4-3-3/4-5-1 (P<0.05) and a 4-2-3-1 formation (P<0.01). In general, the findings suggest that physical performance in the reference team was not greatly affected by opposition team formation. In contrast, skill-related demands varied substantially according to opponent formation and may have consequences for tactical and technical preparation and team selection policies.